Between Strict and Flexibilty: A Comparative Insight of Qawa'id al-Fiqhiyyah in Islamic Banking Practices of Saudi Arabia and Pakistan - suparman, Suparman Kholil; Hersi, Mohammed (Institut Agama Islam Negeri Parepare, 2024)
Purpose – This study aims to analyze how Islamic legal maxims are implemented in the banking sectors of Saudi Arabia and Pakistan, with comparative insights from Indonesia and Malaysia Method – Using a qualitative comparative approach, this research examines fatwas, regulatory frameworks, and governance structures to assess the operationalization of key legal maxims such as al-umuru bi maqasidiha (matters are judged by their objectives) and la darar wa la dirar (there should be neither harming nor reciprocating harm).. Findings – The findings reveal significant differences in the rigidity and flexibility of sharia interpretations across the studied countries. Saudi Arabia adheres to a classical and strict fiqh-based framework, ensuring minimal deviation from traditional rulings. Pakistan, in contrast, integrates modern financial needs within its Islamic banking structure, allowing for greater adaptability. Indonesia and Malaysia offer a middle ground, where sharia compliance is integrated with financial technology and regulatory innovations, ensuring broader financial inclusion. These variations demonstrate the impact of socio-economic and institutional frameworks on the application of Islamic legal principles in banking governance. Practical implications – The study contributes to the discourse on Islamic legal pluralism, showing that sharia compliance in banking is shaped by both legal tradition and economic necessities. Its novelty lies in providing a comparative analysis of different national models. The implications suggest that future regulatory frameworks should balance sharia adherence with financial sustainability, ensuring that Islamic banking remains both ethically grounded and economically competitive in the global market. Originality/value – Its novelty lies in providing a comparative analysis of different national models, illustrating how Islamic legal maxims remain relevant but are applied differently based on institutional and economic priorities